2007
DOI: 10.1037/0002-9432.77.4.610
|View full text |Cite
|
Sign up to set email alerts
|

Substance abuse and psychosocial impairments among clients with schizophrenia.

Abstract: Substance abuse is one of the most common comorbid conditions among clients with schizophrenia. This study assessed correlates of current substance abuse severity not evaluated in past research (e.g., manic symptoms, traumatic stress, self-care deficits, interpersonal relationship problems), as well as factors previously shown to be associated with substance abuse among clients with schizophrenia (e.g., age, gender, depressive symptoms, psychotic symptoms, work/school problems, legal problems). Multiple regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…The final significant association was between problematic substance use and problems with occupational and recreational activities. Reduced uptake of vocational and social activities by dually diagnosed patients, as well as difficulties with employment or school-life have also been shown in previous research (Schwartz et al, 2007;Swartz et al, 2006b).…”
Section: Current Psychosocial Functioningsupporting
confidence: 72%
See 1 more Smart Citation
“…The final significant association was between problematic substance use and problems with occupational and recreational activities. Reduced uptake of vocational and social activities by dually diagnosed patients, as well as difficulties with employment or school-life have also been shown in previous research (Schwartz et al, 2007;Swartz et al, 2006b).…”
Section: Current Psychosocial Functioningsupporting
confidence: 72%
“…eating and cleaning) and more complex skills such as budgeting, which might contribute to the financial difficulties also noted. Schwartz et al (2007) also found an association between substance abuse and a deficit in self-care in patients with schizophrenia.…”
Section: Current Psychosocial Functioningmentioning
confidence: 83%
“…Regarding bipolar disorder specifically, two studies revealed contradictory results as to whether alcohol use was correlated with mania (Reich, Davies, & Himmelhoch, 1974) or depression (Mitchell, Brown, & Rush, 2007). Research has also revealed low-to-moderate positive correlations between substance use and positive symptoms of schizophrenia, depression, mania, and stress reactions in 223 clients diagnosed with schizophrenia (Schwartz, Hilscher, & Hayhow, 2007). Based on these data, associations among various symptoms of mood disorders and substance use show no clear pattern.…”
Section: Substance Use By Diagnosis In People With Severe Mental Illnessmentioning
confidence: 96%